2018
DOI: 10.1128/jmbe.v19i1.1324
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Activities that Promote Metacognitive Skills Impact Lower-Performing Students in an Introductory Biology Course

Abstract: This study explores the impacts of repeated curricular activities designed to promote metacognitive skills development and academic achievement on students in an introductory biology course. Prior to this study, the course curriculum was enhanced with pre-assignments containing comprehension monitoring and self-evaluation questions, exam review assignments with reflective questions related to study habits, and an optional opportunity for students to explore metacognition and deep versus surface learning. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 16 publications
5
35
0
Order By: Relevance
“…Research investigating student calibration and its effect on science classroom performance has shown that the lowest-performing students in introductory biology and chemistry courses were most likely to overestimate their specific content knowledge, exam performance, overall grades, and perceived class rank, while the highest-performing students tended to underestimate themselves in these areas (Jensen and Moore, 2008; Bell and Volckmann, 2011; Ziegler and Montplaisir, 2014; Siegesmund, 2016; Dang et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research investigating student calibration and its effect on science classroom performance has shown that the lowest-performing students in introductory biology and chemistry courses were most likely to overestimate their specific content knowledge, exam performance, overall grades, and perceived class rank, while the highest-performing students tended to underestimate themselves in these areas (Jensen and Moore, 2008; Bell and Volckmann, 2011; Ziegler and Montplaisir, 2014; Siegesmund, 2016; Dang et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This understanding is important for understanding the learning material in the next meeting, so that the questions raised become more qualified. Finally, evaluating activity through posing questions to oneself and related to the content of the learning material familiarizes the pre-service teachers to make evaluative questions (Chin & Brown, 2002;Dang et al 2018). Therefore, it is normal to find many types of questions that require a high level of thinking in the QASEE class.…”
Section: Question Types Based On Cognitive Process Dimensionmentioning
confidence: 99%
“…Furthermore, the extending activity, where there is a transfer of knowledge owned into a new context, also requires the involvement of metacognitive activities, such as planning, monitoring, and evaluating (Ramocki, 2007). Finally, the evaluating activity which is packaged in the form of selfreflection on learning experiences is reported as an important component in encouraging the improvement of metacognition (Dang et al 2018;Duman & Semerci, 2019;Zhang & Patrick, 2012). Therefore, it is normal that many reflective QM questions are found in the QASEE class because its syntax is built on the elements of metacognition.…”
Section: Types Of Questions Based On Knowledge Dimensionsmentioning
confidence: 99%
“…Intentional incorporation of learning strategies that promote metacognition (Cook, Kennedy, & McGuire, 2013;Dang, Chiang, Brown, & McDonald, 2018;Mynlieff, Manogaran, St Maurice, & Eddinger, 2014) and study skills (Sebesta & Speth, 2017) have been shown to improve learning for many students in science courses; and some strategies, such as an increase in course structure, have been found to close the achievement gap for black students and firstgeneration students (Eddy & Hogan, 2014).…”
Section: Evidence-based Educational Practicesmentioning
confidence: 99%